Burden of perianal Staphylococcus aureus colonization in nursing home residents increases transmission to healthcare worker gowns and gloves. (7th December 2020) - Kim, Justin J.; Johnson, J. Kristie; Stucke, Emily M.; Sorkin, John D.; Zhao, LiCheng; Lydecker, Alison; Mody, Lona; Roghmann, Mary-Claire
Abstract: Objective: To evaluate the effect of the burden of Staphylococcus aureus colonization of nursing home residents on the risk of S. aureus transmission to healthcare worker (HCW) gowns and gloves. Design: Multicenter prospective cohort study. Setting and participants: Residents and HCWs from 13 community-based nursing homes in Maryland and Michigan. Methods: Residents were cultured for S. aureus at the anterior nares and perianal skin. The S. aureus burden was estimated by quantitative polymerase chain reaction detecting the nuc gene. HCWs wore gowns and gloves during usual care activities; gowns and gloves were swabbed and then cultured for the presence of S. aureus . Results: In total, 403 residents were enrolled; 169 were colonized with methicillin-resistant S. aureus (MRSA) or methicillin-sensitive S. aureus (MSSA) and comprised the study population; 232 were not colonized and thus were excluded from this analysis; and 2 were withdrawn prior to being swabbed. After multivariable analysis, perianal colonization with S. aureus conferred the greatest odds for transmission to HCW gowns and gloves, and the odds increased with increasing burden of colonization: adjusted odds ratio (aOR), 2.1 (95% CI, 1.3–3.5) for low-level colonization and aOR 5.2 (95% CI, 3.1–8.7) for high level colonization. Conclusions: Among nursing home patients colonized with S. aureus, the risk of transmission to HCW gowns and gloves was greater from those colonized with greater quantities of S. aureus on the perianal skin. Our findings inform future infection control practices for both MRSA and MSSA in nursing homes.